The Interest of Young Agricultural Entrepreneurs (Young Farmers) on Chili Agribusiness in Kabupaten Garut - Ait Maryani; Dedy Kusnadi; Wida Pradiana (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
The study aims at analyzing the descriptions of the interests of young agricultural entrepreneurs (young farmer) and discovering the factors affecting their interest in chili agribusiness. The study was conducted in Kabupaten Garut from June to November, 2019. This study employs a quantitative approach. In this study, population was 1.376 of young agricultural entrepreneurs (young farmer) aged under 40 in chili production centers. Sample for this study was 233 people obtained by calculating following Slovin. The samples were scattered in sub-district of Banyuresmi (79 people), Wanaraja (72 people) and Cikajang (83 people). Sampling technique employed was proportional random sampling. Primary data were collected from respondents through direct interviews and focus group discussion (FGD). The research variables consisted of individual characteristics, external characteristics, and the interests of young agricultural entrepreneurs (young farmer). The collected data were analyzed by utilizing descriptive statistical analysis and multiple regression. The results of the study concluded show that most of the respondents stated their interest were at a moderate level. The average age of young agricultural entrepreneurs (young farmer) is 31.47 years. The majority are still elementary school educated, and most of them have never been involved in organizations and never joined apprenticeship/courses/training. However, cosmopolitan attitude is in the high category. The interest of young agricultural entrepreneurs (young farmer) is affected by institutional, non-formal education, cosmopolitan and external factors including government support, availability of infrastructure, agricultural extension, easy access to information, community leaders and production markets.